KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI GURU PADA SMP NEGERI 2 SIMEULUE TIMUR - Karina Purwanti; Murniari AR; Yusrizal Yusrizal (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2014)
School head master leadership has an important role in improving teacher’s competence. The purpose of this study is to know the program of the school headmaster in improving the teacher’s competence, the strategy and the policy of head master in improving the competence of teachers. The approach used in this study is a qualitative approach with descriptive methods. The data were collected from interviews, observations, and documentations. The subject of the study were the school head master, vice of the school head master, senior teacher, chairman of MGMPs, and teachers. The results show that (1) the school head master program is structured as a reference to enhance the competence of teachers, which is implemented on the teachers empowerment. The empowerment of the teachers program is implemented through engaging the teachers as decision maker and training them to be responsible for the school development through formulating program by teachers and school staffs. (2) the the principal strategy to improve the competence of teachers conducted through some efforts such as training the teachers and skill for the teachers, giving motivation and guiding discipline education. (3)the policy of the school head master in improving the teachers competence being carried out was by involving the teachers in arranging vision and mission, the school target, formulate the school curriculum. The school head master give the opportunity to the teachers to be actively participate, open minded, and cooperate in reaching the school vision.